Contact allergy to antifungals: Results of a 12‐year retrospective study. (10th March 2022) - Gomes, Tiago Fernandes; Calado, Rebeca; Matos, Ana Luísa; Gonçalo, Margarida
Abstract: Background: Contact allergy has been reported as a side effect of topical antifungals (TAFs), although most evidence has come from small case series. Objective: To investigate the frequency and associated factors of contact allergy to TAFs. Methods: We performed a retrospective analysis of the data of the Contact Allergy Unit of a University Dermatology Department between January 2009 and April 2021. From a cohort of 3788 patients tested in our unit, aimed testing was performed in 482 patients using TAFs from Chemotechnique Diagnostics (Vellinge, Sweden), allergEAZE, and, in some cases, commercial preparations 'as is'. Results: Contact allergy to antifungals was found in 27 patients (0.71% of consecutively tested patients and 5.6% of those who had aimed testing). Foot and leg eczema were the clinical presentation in 12 (44.4%) and 10 (37.0%) patients, respectively. Positive reactions were observed mostly with econazole nitrate 1% alcohol (51.9%), miconazole 1% alcohol (48.9%), tioconazole 28% solution (40.7%), and clotrimazole 5% pet. (18.5%). Fifteen patients (55.6%) had sensitization to more than one antifungal. Conclusions: Contact allergy to antifungals was uncommon and occurred mostly associated with foot dermatitis. Most patients were sensitized to more than one chemical, particularly to azoles, which may limit future choices of TAF treatment. Abstract : Contact allergy to antifungals was found in 0.71% of consecutively tested patients and in 5.6% of those who had aimed testing. Foot and leg eczema were the clinical presentation in 44.4% and 37.0% patients, respectively. Positive reactions were observed mostly with econazole nitrate 1% alc. (51.9%), miconazole 1% alc. (48.9%), tioconazole 28% solution (40.7%) and clotrimazole 5% pet. (18.5%). Sensitization to more than one antifungal was observed in 55.6% of the patients.